2009
DOI: 10.2337/db08-1228
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ceramides Are Elevated in Obese Subjects With Type 2 Diabetes and Correlate With the Severity of Insulin Resistance

Abstract: OBJECTIVE-To quantitate plasma ceramide subspecies concentrations in obese subjects with type 2 diabetes and relate these plasma levels to the severity of insulin resistance. Ceramides are a putative mediator of insulin resistance and lipotoxicity, and accumulation of ceramides within tissues in obese and diabetic subjects has been well described.RESEARCH DESIGN AND METHODS-We analyzed fasting plasma ceramide subspecies by quantitative tandem mass spectrometry in 13 obese type 2 diabetic patients and 14 lean h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

41
468
4
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 558 publications
(518 citation statements)
references
References 56 publications
41
468
4
5
Order By: Relevance
“…For example, serum C16:0 and C18:0 ceramide and C18:0 sphingomyelin were recently found to be positively correlated with the markers of muscle NF‐κB activation, suggesting that these specific species could activate the intracellular inflammation (Bergman et al ., 2015). Furthermore, in a previous study, the levels of C18:0, C20:0, C24:1, and total ceramides were found to be elevated in type 2 diabetic subjects compared to controls and were inversely correlated with insulin sensitivity, concluding that these species may contribute to insulin resistance through the activation of inflammatory mediators, such as TNF‐alpha (Haus et al, 2009). In addition, C16:0 and C18:0 ceramides have been mechanistically linked to systemic metabolic health in genetic models (Xia et al ., 2015) and with insulin resistance in the muscle in obesity (Coen et al ., 2010).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, serum C16:0 and C18:0 ceramide and C18:0 sphingomyelin were recently found to be positively correlated with the markers of muscle NF‐κB activation, suggesting that these specific species could activate the intracellular inflammation (Bergman et al ., 2015). Furthermore, in a previous study, the levels of C18:0, C20:0, C24:1, and total ceramides were found to be elevated in type 2 diabetic subjects compared to controls and were inversely correlated with insulin sensitivity, concluding that these species may contribute to insulin resistance through the activation of inflammatory mediators, such as TNF‐alpha (Haus et al, 2009). In addition, C16:0 and C18:0 ceramides have been mechanistically linked to systemic metabolic health in genetic models (Xia et al ., 2015) and with insulin resistance in the muscle in obesity (Coen et al ., 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Our findings are substantially in keeping with a number of previous studies in animal models and humans showing that plasma levels of ceramides are increased in obesity (Samad et al ., 2006; Haus et al ., 2009; Huang et al ., 2011). In fact, obese persons frequently have lower aerobic capacity and mitochondrial dysfunction and the cause of such dysfunction is less than clear.…”
Section: Discussionmentioning
confidence: 99%
“…Increased caloric intake from saturated fat can activate hepatic ceramide synthesis in overweight subjects (Haus et al. 2009; Holland et al. 2011), and subsequently increase lipoprotein ceramide packaging and export (Boon et al.…”
Section: Resultsmentioning
confidence: 99%
“…These proposed mechanisms are consistent with data from several studies that have reported elevated circulating ceramide in obese adolescents, adults with type 2 diabetes, or rodents with NAFLD (Haus et al. 2009; Lopez et al. 2013; Kasumov et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation